Rare Traumatic Pulmonary Pseudocyst in a Seven-year-old Child - Enis Ademoğlu; Mehmet Muzaffer İslam; Gökhan Aksel; Serkan Emre Eroğlu (Oman Medical Journal, 2023)
Traumatic pulmonary pseudocyst is a rare type of parenchymal injury, estimated to occur in 0.1% of all chest traumas. We report a rare case of traumatic pulmonary pseudocyst in a seven-year-old boy who presented with a chest injury from a traffic accident. He had a scapula fracture, multiple abrasions on his body, and decreased respiratory sounds in the left hemithorax. His Glasgow Coma Scale score was 15. Chest X-ray suggested a 3 × 3.5 cm cavitary lesion. Computed tomography scan revealed a pulmonary pseudocyst in addition to parenchymal contusion and pneumothorax. A Velpeau bandage was applied to the scapula fracture. After five days of in-hospital observation without any thoracic intervention, the patient was discharged free of complications.